Poxviruses - Mercer, Andrew; Schmidt, Axel; Weber, Olaf (Birkhäuser Advances in Infectious Diseases, 2007)
The recent international alarm at the possible use of smallpox as weapon of bioterror has refocused the attention of the scientific community, public health policy makers and the public on poxviruses. In contrast to the threat posed by some of these viruses, other poxviruses show exciting beneficial potential including their use as valuable tools in biomedical research and in the delivery of vaccines. This monograph provides a comprehensive review of the poxvirus family with a particular emphasis on current developments. It includes the latest insights into poxviral molecular biology, diagnosis, therapy, vaccine development and the beneficial exploitation of these viruses in biomedical research. Each chapter is written by a leader in the field. The reviews present all aspects of the field, including historical perspectives, along with summaries of the latest advances. This combination makes the book relevant for graduate students, researchers new to the field and to experienced poxvirologists.